Curriculum Innovation, Instructional Strategy and School Governance on the Technical Competency of On-the-Job Trainees - Marcelo C. Calabit; Raul C. Orongan (International Journal on Integrated Education, 2023)
The primary objective of the study was to identify the fundamental elements influencing the technical competency of trainees prior to the on-the-job training (OJT) program. These factors were examined in connection with innovations in curriculum innovations, instructional strategies and school governance. The study utilized a research design characterized as descriptive-correlation research. Pearson product-moment correlation was utilized to determine the extent of connection between curriculum innovation, instructional strategy, and school governance on trainees’ technical competency. Forever, a regression analysis was conducted to ascertain extent which specific variable most accurately predicted trainees’ technical competency. The findings demonstrated that universities and colleges had fully integrated curriculum innovations to enhance the technical competency of trainees. They had also formulated effective instructional strategies, while school governance ensured the complete implementation of OJT program. As a result, trainees exhibited a significantly proficient technical competency even before commencing the OJT program. This suggests that stronger oversight and collaboration between higher education institutions and host training establishment lead to superior outcomes in terms of technically skilled graduates, thereby facilitating optimal job alignment and the cultivation of highly capable graduates in the future. The study underscored the direct relationship between collaborative efforts, evaluation processes, monitoring mechanisms, and the enhancement of trainee’s technical competency.